Shaping Tradition : Civil Society, Community and Development in Colonial Northern Ghana, 1899-1957 - Grischow, Jeff, (African Social Studies Series ;, 2006)
Using Northern Ghana as a case study, this book challenges the invocation of civil society as a tool for building community in the name of development. Far from equating civil society with community, colonial officials used the doctrine of community against African civil society. For colonial officers, civil society represented the corruption of authentic development, which could be avoided only by protecting traditional peasant communities in the face of economic transformation. The book charts this colonial program, from the creation of "native states" in the early twentieth century to an ambitious agricultural mechanisation scheme in the late 1940s. In its challenge to current writing on civil society, the study offers an important contribution to African history and development studies.